Study of the process e+e−→KS0KS0π+π− in the c.m. energy range 1.6–2.0 GeV with the CMD-3 detector - R.R. Akhmetshin; A.N. Amirkhanov; A.V. Anisenkov; V.M. Aulchenko; V.Sh. Banzarov; N.S. Bashtovoy; D.E. Berkaev; A.E. Bondar; A.V. Bragin; S.I. Eidelman; D.A. Epifanov; L.B. Epshteyn; et al. (Physics Letters B, 2020)
The cross section of the process e+e−→KS0KS0π+π− has been measured using a data sample of 56.7 pb−1 collected with the CMD-3 detector at the VEPP-2000 e+e− collider. 596±27 and 210±18 signal events have been selected with six and five detected tracks, respectively, in the center-of-mass energy range 1.6–2.0 GeV. The total systematic uncertainty of the cross section is about 10%. The study of the production dynamics confirms the dominance of the K⁎(892)+K⁎(892)− intermediate state.